2022
DOI: 10.1371/journal.pone.0267475
|View full text |Cite
|
Sign up to set email alerts
|

Vγ9Vδ2 T cells expressing a BCMA—Specific chimeric antigen receptor inhibit multiple myeloma xenograft growth

Abstract: Vγ9Vδ2 T cells are immune effector cells capable of killing multiple myeloma (MM) cells and have been tested in clinical trials to treat MM patients. To enhance the MM cell killing function of Vγ9Vδ2 T cells, we introduced a BCMA-specific CAR into ex vivo expanded Vγ9Vδ2 T cells through electroporation of the CAR-encoding mRNA. The modified Vγ9Vδ2 T cells displayed a high cytolytic activity against BCMA-expressing MM cell lines in vitro, while sparing BCMA-negative cells, including normal B cells and monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similarly, some of these approaches are also relevant to products relying on genetic manipulation of the native TCR itself ( 150 152 ). Finally, some of these BCMA-specific innovations may be applicable to other types of CAR-transduced lymphocytes as well: for example, Natural Killer cells, invariant NK T cells, and gamma-delta T cells ( 153 156 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some of these approaches are also relevant to products relying on genetic manipulation of the native TCR itself ( 150 152 ). Finally, some of these BCMA-specific innovations may be applicable to other types of CAR-transduced lymphocytes as well: for example, Natural Killer cells, invariant NK T cells, and gamma-delta T cells ( 153 156 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sharing innate-like and adaptive-like immune functions makes Vγ9Vδ2 T cells very attractive candidates for genetic engineering ( 134 ). Vγ9Vδ2 T cells have successfully been armed with CAR to target the B-cell Maturation Antigen (BCMA) in MM and CD123 in AML ( 135 , 136 ). Interestingly, in vitro data and in vivo mouse models have shown that, unlike conventional anti-CD19 CAR-T cells, ZA-stimulated anti-CD19 Vγ9Vδ2 CAR-T cells from healthy donors can target both CD19 + and CD19 - allogeneic leukemia cells via the non-specific MHC-independent cytotoxic activity elicited by pAgs stimulation ( 137 ).…”
Section: Strategies To Bring Vγ9vδ2 T-cell Immune Interventions To Pr...mentioning
confidence: 99%